2015
DOI: 10.1371/journal.pone.0121077
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase-4 Inhibitor Decreases Abdominal Aortic Aneurysm Formation through GLP-1-Dependent Monocytic Activity in Mice

Abstract: Abdominal aortic aneurysm (AAA) is a life-threatening situation affecting almost 10% of elders. There has been no effective medication for AAA other than surgical intervention. Dipeptidyl peptidase-4 (DPP-4) inhibitors have been shown to have a protective effect on cardiovascular disease. Whether DPP-4 inhibitors may be beneficial in the treatment of AAA is unclear. We investigated the effects of DPP-4 inhibitor sitagliptin on the angiotensin II (Ang II)-infused AAA formation in apoE-deficient (apoE-/-) mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 45 publications
4
45
0
1
Order By: Relevance
“…In addition to their glucose-lowering action, DPP-4 inhibitors have been demonstrated to play a protective role in cardiovascular diseases, including hypertension [44], abdominal aortic aneurysm [45], cardiomyopathy [46], atherosclerosis [47], and peripheral vascular disease [48], via both GLP-1-dependent and GLP-1-independent pathways due to their diverse, widely distributed, and pleiotropic actions [49]. Many in vivo and in vitro studies also found that DPP-4 inhibitors can prevent organ fibrosis, including cardiac fibrosis [50,51], hepatic fibrosis [52], and kidney fibrosis [53].…”
Section: Biology Of Dpp-4mentioning
confidence: 99%
“…In addition to their glucose-lowering action, DPP-4 inhibitors have been demonstrated to play a protective role in cardiovascular diseases, including hypertension [44], abdominal aortic aneurysm [45], cardiomyopathy [46], atherosclerosis [47], and peripheral vascular disease [48], via both GLP-1-dependent and GLP-1-independent pathways due to their diverse, widely distributed, and pleiotropic actions [49]. Many in vivo and in vitro studies also found that DPP-4 inhibitors can prevent organ fibrosis, including cardiac fibrosis [50,51], hepatic fibrosis [52], and kidney fibrosis [53].…”
Section: Biology Of Dpp-4mentioning
confidence: 99%
“…We also found that the lower α-smooth muscle actin (SMA)-positive vascular area in abdominal aortic aneurysmal sections of SMKO mice treated with Ang II and BAPN accompanied with greater incidence of aortic aneurysm, relative to the control ( Figure XVI in the online-only Data Supplement). Because VSMC apoptosis has previously been shown to be a factor in aneurysm formation by multiple groups, 15,16 this result may reflect the reduced number of VSMCs in aneurysmal regions in SMKO mice. However, we could not confirm so many apoptotic VSMCs in abdominal aortic aneurysmal regions in control mice and SMKO mice in this model (data not shown).…”
mentioning
confidence: 98%
“…Lu et al . observed that treatment with liraglutide for 1 hr decreases chemotaxis, ROS generation, MMP‐2 and MMP‐9 activities using a human monocyte cell line stimulated with Ang‐II.…”
Section: The Impact Of Antidiabetic Drugs On Endothelial Dysfunctionmentioning
confidence: 96%